RESEARCH OF THE INFLUENCE OF FREQUENCY CHARACTERISTICS OF HEARING IN THE PROCESS OF MEASURING THE AUDIOCONTENT LOUDNESS - KOLTSOVA, OLEKSANDRA; KHIVRENKO, RUSLAN; GRACHOV, ARTUR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Nowadays the problem of correct estimation and measurement of TV- and sound broadcasting programmes loudness is of great importance. The European Broadcasting Union (EBU) has established a special investigation group, dealing with loudness estimation and normalization, similarly, ITU emphasizes on the importance of objective measurement of audio program loudness to facilitate program delivery and exchange, and to provide more comfortable listening experience for audiences. In Recommendation ITU-R BS.1770-5 the modern algorithm of objective loudness measurement is described in detail. This algorithm includes frequency weighting of the measured audio signal to assume frequency properties of human auditory system, but such weighting concerns only the lower part of sound frequency band. In this article, the authors raise the question of the necessity of taking into account the dependence of sensitivity of the human auditory system on upper frequencies of the sound band. A brief overview of the existing representations of the frequency response of hearing sensitivity when listening to different types of sound signals is provided. Also in the article are discussed the results of subjective assessment of appreciability of changes in loudness of audio content of different types (speech and music) while changing the audio signal’s level on the upper frequencies of sound band.  In one case the level of audio signal was adjusted according to the equal loudness contour corresponding to 60 phones of loudness level, and in another case, according to one of the variants of the averaged psophometric curve. The results of subjective assessment  for these two cases were compared with each other.For all processed sound fragments, a confidence intervals were calculated based on the indicator of appreciability of changes in loudness, percieved by the listeners, and evaluated the accuracy of the results. Based on the results obtained from subjective assessment, further ways of conducting of the research are proposed.
Keywords: sound loudness; audio content; sensitivity of the human auditory system; sound band; subjective assessment